Predictors of the Development of Major Adverse Cardiac Events following Percutaneous Coronary Intervention - Nouha Azaza; Fahad O. Baslaib; Akram Al Rishani; Mariam Ahmed; Jumana Al-Zainal; Mohamed Aboalela; Marian Gargousa; Geili Abdalla; Nadim Shah (Dubai Medical Journal)
Background: Coronary artery disease remains the greatest cause of morbidity and mortality worldwide despite the growing access to percutaneous coronary intervention (PCI). Data regarding the factors predicting the development of major adverse cardiac events (MACE) in patients undergoing PCI are, however, lacking in the gulf region. In this study, we analyze demographics and risk profile of all patients undergoing PCI in a tertiary cardiovascular center located in Dubai – UAE. In our study, we aimed to analyze the risk profile of all patients undergoing PCI and determine the independent predictors of MACE. Methods: Data were collected prospectively on all patients who underwent PCI in our hospital between September 2017 and September 2018. Patients aged 18 years and above were included in the study and there were no exclusion criteria. The definition of MACE was a composite of death, in-hospital recurrent myocardial infarction (MI), in-hospital target vessel revascularization (TVR), and stroke. The patients’ characteristics, risk factor, and demographics were analyzed to identify the predictors of MACE using logistic regression model which is presented in odds ratio. Results: Data were available for 789 patients. Of these, 741 (94%) were male. The mean age was 52 ± 11 years. Twenty-two (3%) patients died, 7 (1%) had an in-hospital recurrent MI, 6 (1%) had in-hospital TVR, and 1 (0.1%) had a stroke. Of the patients who died, 16 (73%) patients presented with cardiogenic shock. Major adverse cardiovascular events occurred in 29 (3.7%) patients. In the multivariable regression model, only cardiogenic shock (odds ratio [OR] = 32.43) and the presence of diabetes mellitus (OR = 3.36) were predictors of MACE. Conclusion: Our study showed that cardiogenic shock and diabetes mellitus are the independent predictors of MACE in patients undergoing PCI.